Ludotopia. O granicy świata gry - Maj, Krzysztof M. (Przestrzenie Teorii, 2021)
The essay presents an overview of the possible meanings and applications of the newly-coined term ‘ludotopia’, i.e. a “dialectical entanglement of game and space” – which challenges the boundaries of two neighbouring worlds: storyworld and gameworld. Seeking to trace the limitations of a thus defined gaming space, the author proceeds by reflecting upon the end of the game, or, more precisely, the endgame, in order to reconcile it with a notion of horismós (ὁρισμός) popular in more hermeneutically aligned video game studies. While doing so, the paper delivers an analysis of Assassin’s Creed: Odyssey showing three distinct stages in which a ludotopia can be opened towards more advanced world-building: (1) exploration and map reveal; (2) synchronisation of intelligible tags; and (3) renewal of narrative motivation. Thanks to a world-centered approach to the interpreted video game, the essay addresses how players inhabit, traverse, explore, and understand the surrounding ludic reality, rather than focusing on video game mechanics or procedures that affect their gameplay. In the end, a precise distinction between the storyworld and gameworld is introduced in order to reevaluate the ways both terms overlap with the aforementioned interpretation of ludotopia.